The study of correlation between chromatin compactization failures and sperm aneuploidies in men with low fertility - Феськов, О. М.; Жилкова, Є. С.; Сотнік, Н. М.; Федота, О. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The dependence between the presence of sperm aneuploidies and the level of sperm DNA fragmentation in ejaculate in different age groups of men with low reproductive function has been examined. The direct correlation for chromatin compactization failures and sperm chromosomes aberrations has been found out for men elder than 35 years old. The rising of quantity of aneuploid spermatozoa leads to increase of the sperm DNA fragmentation level. The critical clinically significant age that leads to male infertility is 35 years old.